Climate Change and its Impact on Tourism in Nepal - K.C., Anup (Journal of Tourism and Hospitality Education, 2017)
Climate change is a burning issue which had affected different sectors of the environment. It is observed in Nepal in the form of increased frequency of natural disasters, rise in temperature and change in rainfall patterns, shifting of tree line and unfavorable weather change phenomena. It had affected agriculture, hydropower, tourism and livelihood of people in Nepal. Tourism is a travel to a place for the purpose of business, vacation and other activities. It generates enterprise and employment, increases income and helps in sustaining livelihood of local people. There is a close relationship between climate and tourism in ecosystem tourism, coastal tourism, mountain tourism and nature-based tourism. Climate change brings more risks than opportunities by causing regional and seasonal shifts in tourist flows. This paper is based on the review of researches on climate change and tourism. Climate change had caused shift in destination choice of tourists. It had reduced barrier of winter tourism in Nepal in short term. But, unfavorable weather change phenomena had taken lives of many tourists in Nepal and had caused discomfort in transportation in mountain regions. It would decrease the flow of tourists in long term and decrease the income from tourism. It will further cause adverse impact on livelihood of tourism dependent people. To minimize the adverse impact of climate change on tourism, appropriate preventive measures, rescue measures and early warning systems should be implemented in mountain tourism in Nepal. Journal of Tourism and Hospitality Education Vol. 7, 2017, page: 25-43